Metode Pembelajaran Aktif: Partisipasi Siswa Lebih Penting dari Sekadar Mendengarkan: Partisipasi Siswa Lebih Penting dari Sekadar Mendengarkan - Hidayah, Shilfina (Maliki Interdisciplinary Journal, 2025)
This article discusses the importance of active learning methods to increase educational effectiveness compared to more passive traditional methods. Active learning, which involves interaction, collaboration, and hands-on application, provides a more effective approach to motivating and engaging students. Through a variety of methods such as group discussions, project-based learning, and simulations, students can not only work harder but also develop important critical and creative thinking skills. By summarizing various case studies and real-life examples, this article shows how active learning can be effectively integrated into the curriculum and have a significant positive impact on the teaching and learning process.